TIMOR-LESTE IN THE XXI CENTURY: ISSUES AND PROSPECTS - Chu, Thanh Van; Tran, Thi Thuy; Bui, Thi Thanh Dung (VNU Journal of Foreign Studies, 2026)
The process of Timor-Leste's independence from Indonesia has not only shaped the dynamics of the XXI century global landscape. Still, it has also been a historical reality influenced by internal and external factors, notably Australian support - a traditional middle power. However, the achievement of Timor-Leste's independence has challenged Australia's relations with Indonesia. Despite being the least developed country in Southeast Asia and grappling with economic struggles, Timor-Leste aspires to overcome these hurdles after 19 years of independence and build a prosperous and robust nation, as outlined in the Timor-Leste Strategic Development Plan extending until 2030. The paper aims to evaluate the issues of Timor-Leste in the twenty-first century, considering geopolitical conditions, post-independence impacts, and issues related to international integration.